2010
DOI: 10.1007/s11307-010-0299-8
|View full text |Cite
|
Sign up to set email alerts
|

AuNP-DG: Deoxyglucose-Labeled Gold Nanoparticles as X-ray Computed Tomography Contrast Agents for Cancer Imaging

Abstract: Results from this study demonstrate enhanced uptake of 2-DG-labeled gold nanoparticle by cancer cells in vitro and warrant further experiments to study the exact molecular mechanism by which the AuNP-DG is internalized and retained in the tumor cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(74 citation statements)
references
References 24 publications
1
73
0
Order By: Relevance
“…In vitro cell labeling studies demonstrated that cells positive for the targeted receptor were able to internalize a greater mass of AuNPs compared with cells without the receptor or when treated with nontargeted AuNPs [47][48]61,[63][64][65][66][67][68][69][70][71][72]. AuNPs targeted to mineral surfaces were shown to reach a saturation point in the surface density of AuNPs labeling mineral surfaces in vitro [32,73], similar to the saturation point observed for the nontargeted delivery of AuNPs to cells.…”
Section: Deliverability and Targetingmentioning
confidence: 81%
See 1 more Smart Citation
“…In vitro cell labeling studies demonstrated that cells positive for the targeted receptor were able to internalize a greater mass of AuNPs compared with cells without the receptor or when treated with nontargeted AuNPs [47][48]61,[63][64][65][66][67][68][69][70][71][72]. AuNPs targeted to mineral surfaces were shown to reach a saturation point in the surface density of AuNPs labeling mineral surfaces in vitro [32,73], similar to the saturation point observed for the nontargeted delivery of AuNPs to cells.…”
Section: Deliverability and Targetingmentioning
confidence: 81%
“…Other molecules that have been investigated for improving colloidal stability include gum arabic [59,128], polyacrylic acid [63], polysaccharides [20,48] and polyvinyl alcohol [32,73,84,[129][130][131]. AuNPs have been surface functionalized with peptides [21,72], antibodies [23,47,[63][64][69][70], saccharides [20,48,[66][67], lipoproteins [22,132] and numerous small molecules [32,61,71,73,[122][123]125,[129][130][131] for active targeting. Molecular ligands can be strategically chosen for target-specific binding to a site of interest, including cancerous cells or tumors [21,33,[47][48]61,[63][64][65][66][67][68][69]…”
Section: Surface Functionalizationmentioning
confidence: 99%
“…5 E-selectin peptides graed on liposome surface, 6 or 2-deoxy-D-glucose onto gold NPs 7 have also shown interesting accumulation in cancer cells due to their enhanced glucose consumption. Specic targeting of pancreatic ductal adenocarcinoma can be performed through plectin-1 targeted peptides (PTP) at the surface of hybrid iron oxide/polymeric NPs.…”
Section: Introductionmentioning
confidence: 99%
“…Cells were allowed to incubate with targeted AuNP before being imaged. Glucose allowed for an increased uptake of AuNP to cells, resulting in a 4-fold increase in CT attenuation in these targeted cells over nontargeted trials [40]. Li et al similarly described attachment of 2-DG to AuNP and subsequent uptake into A-549 cells in vitro.…”
Section: Cancer Targeted Gold Nanoparticles Formulationsmentioning
confidence: 99%